Diagnostic Accuracy of Different Soluble fms-Like Tyrosine Kinase 1 and Placental Growth Factor Cut-Off Values in the Assessment of Preterm and Term Preeclampsia: A Gestational Age Matched Case-Control Study - Huhn, Evelyn A.; Kreienbühl, Andrea; Hoffmann, Ina; Schoetzau, Andreas; Lange, Soeren; Martinez de Tejada, Begona; Hund, Martin; Hoesli, Irene; Lapaire, Olav (Frontiers in Medicine, 2018)
INTRODUCTION: The objective was to investigate the diagnostic accuracy of different thresholds of the soluble vascular endothelial growth factor receptor-1 (sFlt-1) and the placental growth factor (PlGF) in preterm (<37 weeks) and term (>37 weeks) preeclampsia (PE). MATERIALS AND METHODS: A nested case-control study was performed from a high-risk Swiss cohort. Only blood samples on the day of PE diagnosis were included. The primary outcome was to verify the diagnosis using the recently proposed cut-off values for PE (sFlt-1:PlGF ratio of >85 in <34 weeks or >110 in >34 weeks), and the gestational age dependent centiles. RESULTS: Thirty-four women with preterm PE were matched with 64 controls and 25 women with term PE with 45 controls. The test performance of the sFlt-1:PlGF ratio in preterm PE was very good (AUROCC of 0.95). The sFlt-1:PlGF ratio could adequately predict adverse fetal or neonatal outcome. In term PE, sFlt-1 alone showed a slightly better diagnostic accuracy with an AUROCC of 0.84. Almost all women with a sFlt-1:PlGF ratio above threshold delivered during the following week. DISCUSSION: In pregnant women with high risk of developing PE, the sFlt-1:PlGF ratio and sFlt-1 levels help clinicians to confirm the diagnosis of imminent preterm PE and can additionally be used to rule out PE at term.